2011
DOI: 10.1029/2011ja017047
|View full text |Cite
|
Sign up to set email alerts
|

Lunar tide in the equatorial electrojet in relation to stratospheric warmings

Abstract: [1] The relationship between sudden stratospheric warmings (SSWs) and large-amplitude lunar tides in the equatorial electrojet (EEJ) is studied. Analysis of ground magnetometer data shows that the lunar tide in the EEJ is maximum during the northern winter season except in the Pacific Ocean region. Since SSWs are also a northern winter phenomenon, it is suggested that the relation between the large lunar tide in the EEJ and the SSW may possibly be coincidental. The lunar tide in the geomagnetic variations at H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 23 publications
(38 reference statements)
8
80
0
Order By: Relevance
“…The total current intensity is largest during the Northern Hemisphere winter. The lunar modulation of the equatorial electrojet is also greatest during the northern winter, except in the West Pacific region (Rastogi and Trivedi 1970;Stening 2011). The strong L currents during the northern winter is probably contributed by the big L days in which the amplitude of L is several times larger than other normal days ( (Bartels and Johnston 1940);Onwumechili 1964).…”
Section: Eejmentioning
confidence: 97%
See 1 more Smart Citation
“…The total current intensity is largest during the Northern Hemisphere winter. The lunar modulation of the equatorial electrojet is also greatest during the northern winter, except in the West Pacific region (Rastogi and Trivedi 1970;Stening 2011). The strong L currents during the northern winter is probably contributed by the big L days in which the amplitude of L is several times larger than other normal days ( (Bartels and Johnston 1940);Onwumechili 1964).…”
Section: Eejmentioning
confidence: 97%
“…They noted that there are some years when a lunar tidal amplification occurs without a stratospheric sudden warming event and other years when there is no lunar tidal amplification during a stratospheric sudden warming event. Stening (2011Stening ( ), analyzing equatorial data during 1960Stening ( -2009, also noted that not all stratospheric sudden warmings cause a counter electrojet event. A numerical study by Pedatella and Liu (2013) showed that the lunar tidal amplification depends on the phase of the moon relative to the timing of the stratospheric sudden warming.…”
Section: Stratospheric Sudden Warming Effectmentioning
confidence: 99%
“…Moreover, January is also the usual time when stratospheric sudden warming (SSW) occurs. It has been widely reported that SSW modify the mean stratospheric temperature and zonal wind conditions, leading to an enhancement of the lunar tide magnitudes (e.g., Fejer et al, 2010;Stening, 2011;Yamazaki et al, 2012;Park et al, 2012). On the other hand, in the absence of a SSW event and when the Earth is at the furthest distance from the Sun (aphelion) during June solstice, the lunar tide influence on the EEJ is very small.…”
Section: Seasonal Variability In the Lunar Tidementioning
confidence: 99%
“…Rastogi and Trivedi (1970), using limited data obtained during the International Geophysical Year and the International Geophysical Cooperation (IGY-IGC) period (on average, 1 year of data for each station), reported significant longitudinal variability in the lunar tide. Stening (2011), using magnetometer data, also reported about the relationship between sudden stratospheric warmings (SSWs) and large lunar tide amplitude at different longitudes. Recently, Lühr et al (2012), using magnetometer observations onboard the CHAMP satellite, reported longitudinal and solar cycle variability in lunar tidal wave amplitudes and found no significant longitudinal variability in the lunar tidal wave impact on the EEJ.…”
Section: Introductionmentioning
confidence: 99%
“…Fejer et al, 2010Fejer et al, , 2011Stening, 2011;Park et al, 2012;Yamazaki et al, 2012a, b). Stening (2011) pointed out that the relation between the large lunar tide in EEJ and SSW events could be coincidental, while Park et al (2012) confirmed a one-to-one correspondence between the lunitidal enhancement at ionospheric heights and the occurrence of SSW events between 2001-2009. Likewise, Yamazaki et al (2012a investigated the correlation between the amplitude of the geomagnetic lunar tide at Addis Ababa and lower stratospheric parameters and confirmed the occurrence correspondence between SSWs and the enhancement of the geomagnetic lunar tide for the majority of years between 1958-2007.…”
Section: Introductionmentioning
confidence: 99%